Oral functional improvements in lingual hypomobility: a systematic review of surgical, myofunctional, and combined therapies - Angelo Michele Inchingolo; Grazia Marinelli; Lucia Pia Zaminga; Sara Savastano; Francesco Inchingolo; Daniela Di Venere; Gaetano Isola; Andrea Palermo; Gianna Dipalma; Alessio Danilo Inchingolo (Exploration of Medicine, 2026)
Background: Ankyloglossia is a congenital condition characterized by restricted tongue mobility, which may influence oral functions such as speech, swallowing, and oral motor coordination. This systematic review aimed to evaluate oral functional outcomes following surgical and/or myofunctional interventions in individuals with lingual hypomobility. A secondary aim was to assess variability and consistency of functional improvements across different therapeutic approaches. Methods: This systematic review was conducted in accordance with PRISMA guidelines. PubMed, Scopus, and Web of Science were searched between 15 June 2025 and 10 August 2025. Eligible clinical studies (randomized controlled trials, cohort studies, and case series/reports) evaluated lingual frenotomy, frenulectomy, or frenuloplasty, alone or combined with orofacial myofunctional therapy, and reported oral functional outcomes, including tongue mobility, oral posture, swallowing-related tasks, neuromuscular measures, and patient-reported function. Risk of bias was assessed using validated tools (ROBINS-I and RoB 2). Due to heterogeneity in study design and outcome measures, a narrative synthesis was performed. Results: Ten studies involving more than 1,300 participants across pediatric, adolescent, and adult populations were included. The evidence comprised randomized controlled trials, observational studies, and case series. Surgical intervention alone was primarily associated with immediate anatomical and mobility-related improvements. In contrast, combined surgical and myofunctional approaches were more consistently associated with improvements in functional outcomes, including tongue mobility, resting posture, and swallowing-related functions. However, the consistency of these improvements varied across age groups, intervention protocols, and outcome assessment methods. Risk of bias was variable and frequently influenced by heterogeneous diagnostic criteria, nonstandardized interventions, and nonuniform outcome measures. Discussion: Combined surgical and myofunctional interventions appear to be associated with improvements in oral functional outcomes compared with stand-alone approaches. However, due to substantial methodological heterogeneity and limited high-quality evidence, these findings should be interpreted with caution and are primarily applicable to the specific functional domains evaluated.